2010
DOI: 10.4067/s0716-97602010000400014
|View full text |Cite
|
Sign up to set email alerts
|

Internucleotide correlations and nucleotide periodicity in Drosophila mtDNA: New evidence for panselective evolution

Abstract: Analysis for the homogeneity of the distribution of the second base of dinucleotides in relation to the first, whose bases are separated by 0, 1, 2,… 21 nucleotide sites, was performed with the VIH-1 genome (cDNA), the Drosophila mtDNA, the Drosophila Torso gene and the human β-globin gene. These four DNA segments showed highly significant heterogeneities of base distributions that cannot be accounted for by neutral or nearly neutral evolution or by the "neighbor influence" of nucleotides on mutation rates. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…It is probably related to the tertiary structure needed to fold the RNA virus into its capsid. In a second study we found similar correlations until K= 21, in Drosophila melanogaster mtDNA, Gene Torso, and in human beta globin (βHb) gene (Valenzuela, 2010a). However, the significance of the interaction was observed until K = 309 in HIV-1 and until K = 609 in mtDNA (Valenzuela 2010b).…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…It is probably related to the tertiary structure needed to fold the RNA virus into its capsid. In a second study we found similar correlations until K= 21, in Drosophila melanogaster mtDNA, Gene Torso, and in human beta globin (βHb) gene (Valenzuela, 2010a). However, the significance of the interaction was observed until K = 309 in HIV-1 and until K = 609 in mtDNA (Valenzuela 2010b).…”
Section: Introductionmentioning
confidence: 71%
“…Our study seeks to know the sequence information for tertiary or quaternary DNA structures (in relation to non-DNA molecules). We seek to affi rm or refute neutral, nearly neutral or selective evolution (Valenzuela and Santos, 1996, Valenzuela, 1997, 2007, 2010aValenzuela et al, 2010). Unexpectedly, we found a very high correlation between both bases of a dinucleotide separated by 0, 1, 2 …K (K= 35) nucleotide sites in the whole genome of the HIV-1 virus, and in one env gene of this virus (Valenzuela, 2009).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations